“Ce chatoiement linguistique” Les grands auteurs martiniquais entre langue française et langue créole (Altre Modernità, 2019)
The linguistic complexity of the Caribbean context forces any literaryauthor to choose a language (or more languages) in the very wide range offered bythe Creole continuum, from Creole to the European languages that arrived on theislands through colonization. The situation of Creole in the French Antilles isparticularly interesting, because it reveals the history of a denied or silenced language,at times by its own speakers, and also by the great authors of the FrancophoneCaribbean, as we will see analyzing the relationship with Creole and French of authorsof different generations, from Césaire and Glissant to Confiant and Chamoiseau.Instead of judging these authors and their linguistic choices, this article will focus on areading of their complex and sometimes ambiguous relationship with these twolanguages, and on the influence that this has had on the birth of a literature in Creolein Martinique. Reading this relationship through their interviews, with thecharacteristic immediacy and spontaneity of this genre, will help us to read anunstable thought, revealing not only the results of their reflection on the possibilitiesof a single language, but above all the possibility of using this history of oppression asa starting point for a new perception of the role that any language can play inCaribbean literary creation.
Keywords: French; Creole; Francophone literatures; Caribbean literatures; Martinique; interview